Bacillus subtilis EA-CB0575 genome reveals clues for plant growth promotion and potential for sustainable agriculture (2020)
Bacillus subtilis is a remarkably diverse bacterial species that displays many ecological functions. Given its genomic diversity, the strain Bacillus subtilis EA-CB0575, isolated from the rhizosphere of a banana plant, was sequenced and assembled to determine the genomic potential associated with its plant growth promotion potential. The genome was sequenced by Illumina technology and assembled using Velvet 1.2.10, resulting in a whole genome of 4.09 Mb with 4332 genes. Genes involved in the production of indoles, siderophores, lipopeptides, volatile compounds, phytase, bacilibactin, and nitrogenase were predicted by gene annotation or by metabolic pathway prediction by RAST. These potential traits were determined using in vitro biochemical tests, finding that B. subtilis EA-CB0575 produces two families of lipopeptides (surfactin and fengycin), solubilizes phosphate, fixes nitrogen, and produces indole and siderophores compounds. Finally, strain EA-CB0575 increased 34.60% the total dry weight (TDW) of tomato plants with respect to non-inoculated plants at greenhouse level. These results suggest that the identification of strain-specific genes and predicted metabolic pathways might explain the strain potential to promote plant growth by several mechanisms of action, accelerating the development of plant biostimulants for sustainable agricultural. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.